Measuring Islamic Banking Employees’ Satisfaction on the Conversion of Sahara Bank in Benghazi City to Islamic banking and marketing its products: Exploratory Research - الكرغلي صبري جبران محمد; بن عامر نسرين محمد (Tobruk University Journal of Social and Human Sciences, 2021)
The current study aims to measure the satisfaction level of Islamic Banking Staff of Sahara Bank in Benghazi City regarding the conversion of the bank to Islamic banking that comply with the requirements of Islamic law to market products meet customers’ expectations. In order to achieve this goal, descriptive analytical approach was used and Sahara Bank in Benghazi City was selected as a case study, where a questionnaire instrument was directed to Islamic Banking Department’s employees. Statistical Package for Social Sciences (SPSS) was used to analyze the data. The most prominent results of the study were that there was an increase in employees’ satisfaction level regarding the Islamic Banking products offered to customers. The demand level was perceived to be high. It has also become apparent that there are number of obstacles that stand in the way of Sahara bank conversion to Islamic banking. These obstacles have come from multiple sources including: customers, employees, the external environment, regulations, Islamic banking department, some relevant governmental authorities, the bank administration, and finally the weakness of technology. The study concluded with its limitations, and puts forward set of theoretical and practical implications and recommendations.